2007
DOI: 10.1089/cbr.2007.367a
|View full text |Cite
|
Sign up to set email alerts
|

Study of Apoptosis Induced by 188Re-DTPA-DG in MCF-7 Breast Carcinoma and A549 Pulmonary Carcinoma Cells

Abstract: 188Re-DTPA-DG has a significant apoptotic effect on carcinoma cells. 188Re-DTPA-DG is an effective radiopharmaceutical for intratumoral radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A previous study showed that 188 Re-DTPA-DG had an apoptotic effect on carcinoma cells. 26 Both 188 Re and 177 Lu can emit c photons for imaging and b --particles for therapy, but the characteristics of these radionuclides are different. 188 Re is obtained from a 188 W/ 188 Re generator in clinical settings and has a half-life of 0.7083 d, with a complicated decay mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that 188 Re-DTPA-DG had an apoptotic effect on carcinoma cells. 26 Both 188 Re and 177 Lu can emit c photons for imaging and b --particles for therapy, but the characteristics of these radionuclides are different. 188 Re is obtained from a 188 W/ 188 Re generator in clinical settings and has a half-life of 0.7083 d, with a complicated decay mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…They are MAG-3-glucosamine [53], DTPA-glucosamine [54][55][56][57][58], and ECglucosamine (EC-G) [59][60][61]. The structures are shown in Fig.…”
Section: Radiolabeled Glucosamine Analogues As Alternative Chelator-bmentioning
confidence: 99%
“…However, there were neither a tumor model nor human studies to affirm the effectivenss of MAG-3-glucosmaine. Although, DTPA-glucosamine was labeled with 99m Tc and 188 Re, respectively [54][55][56][57][58], it exhibited a faster clearance in animal studies, thus, the tumor registration was low. Again, it has been discovered that radiolabeled EC-G behaves, in certain respects, quite differently than radiolabeded FDG.…”
Section: Radiolabeled Glucosamine Analogues As Alternative Chelator-bmentioning
confidence: 99%